The Relationship between Foreign Direct Investment and Financial Market Development in Emerging Economies - Ayub, Mujtaba (2013)
Our paper investigates the potentially bi-directional causal relationship between Foreign Direct Investment (FDI) and Financial Market Development (FMD, which includes banking sector as well as stock market development) through panel data from 24 emerging economies from around the world. We also use a simultaneous equation model with additional macro-economic and governance indicators as controls to see whether FDI and FMD are determined simultaneously and how these indicators affect this relationship. The causality tests provide evidence for bi-directional causality between FDI and banking sector development variables, while the relationship between FDI and stock market development variables seems to be more uni-directional, i.e. from FDI to FMD. The simultaneous equation model reveals an overall tendency towards a more uni-directional relationship from FDI to FMD, except for a bi-directional relationship between FDI inflows and credit provided by banks to the private sector. Overall, through the use of post-2007 data, our findings add to previous research by tracking the change in overall trends in the FDI-FMD relationship since the global financial crisis. Moreover, our study finds some evidence that improving governance indicators like transparency, institutional efficiency and corruption can improve the development of financial markets in newly developing economies which in turn can be crucial in attracting further FDI inflows. This makes for a strong case for a policy that encourages focus on governance reforms in order to stimulate economic growth and promote financial sophistication in emerging economies.